Applicability of European Society of Cardiology guidelines according to gross national income. (18th November 2022) - van Dijk, Wouter B; Schuit, Ewoud; van der Graaf, Rieke; Groenwold, Rolf H H; Laurijssen, Sara; Casadei, Barbara; Roffi, Marco; Abimbola, Seye; de Vries, Martine C; Grobbee, Diederick E
Abstract: Aims: To assess the feasibility to comply with the recommended actions of ESC guidelines on general cardiology areas in 102 countries and assess how compliance relates to the country's income level. Methods and results: All recommendations from seven ESC guidelines on general cardiology areas were extracted and labelled on recommended actions. A survey was sent to all 102 ESC national and affiliated cardiac societies (NCSs). Respondents were asked to score recommended actions on their availability in clinical practice on a four-point Likert scale (fully available, mostly/often available, mostly/often unavailable, fully unavailable), and select the top three barriers perceived as being responsible for limiting their national availability. Applicability was assessed overall, per World Bank gross national income (GNI) level, and per guideline. A total of 875 guideline recommendations on general cardiology was extracted. Responses were received from 64 of 102 (62.7%) NCSs. On average, 71·6% [95% confidence interval (CI): 68.6–74.6] of the actions were fully available, 9.9% (95% CI: 8.7–11.1) mostly/often available, 6.7% (95% CI: 5.4–8.0) mostly/often unavailable, and 11·8% (95% CI: 9.5–14.1) fully unavailable. In low-income countries (LICs), substantially more actions were fully unavailable [29·4% (95% CI: 22.6–36.3)] compared with high-income countries [HICs, countries 2.4% (95% CI: 1.2–3.7); P < 0.05]. Nevertheless, a proportion of actions with the lowest availability scores were often fully or mostly unavailable independent of GNIs. Actions were most often not available due to lack of reimbursement and other financial barriers. Conclusion: Local implementation of ESC guidelines on general cardiology is high in HICs and low in LICs, being inversely correlated with country gross national incomes. Structured Graphical Abstract: Structured Graphical Abstract Global availability and applicability of ESC guidelines on general cardiology is high in high-income countries and low in low-income countries